Faktor-faktor yang Mempengaruhi Organizational Trust pada karyawan Kantor Imigrasi Kelas I DKI Jakarta - Addittia Padma Wahyudi; Wiwik Robiatul Adawiyah; Dita Oki Berliyanti (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
This study aims to examine the effect of diversity management, ethical leadership and organizational culture on organization trust in Class 1 Immigration Office DKI Jakarta. The samples used in this study were employees at 2 Class 1 Immigration Offices in DKI Jakarta. Sampling used a non-probability sampling method with a purposive sampling technique, namely distributing online questionnaires (google form) to Class 1 DKI Jakarta Immigration Office employees. Testing was carried out using as many as 140 respondents. Methods Data analysis used the regression method which was processed with the help of SPSS 25.0 software. The results of this study indicate that diversity management, CSR and organizational culture have a significant positive effect on organizational trust. Future research is expected to be able to develop research by examining other fields or offices as research objects and increase the number of respondents in order to obtain more accurate results, then other researchers can also add other variables that can also influence organizational trust.